2020
DOI: 10.31883/pjfns/114897
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decarboxylation of Betacyanins in Red Beet Betalain-Rich Extract

Abstract: Red beetroot (Beta vulgaris L.) is the main commercially exploited source of betalain pigments which are produced in the form of concentrates or powders [Ciriminna et al., 2018]. The most abundant pigments present in red beet are betanin (red betacyanin) and vulgaxanthin I (yellow betaxanthin). Due to their satisfying nutritional value and disease-preventing effects, such extracts are regarded benefi cial to human health and applied as food additives, colorants, and dietary supplements [Nemzer et al., 2011]. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 33 publications
2
18
0
Order By: Relevance
“…Based on these assumptions, it can be concluded that the mechanism of betacyanin degradation may be different, and its variants were initially presented in our publications [41,[43][44][45]. In the course of many years of work on decarboxylated compounds, the above-mentioned and many other structures have been confirmed by LC-MS and/or NMR methods [6,46,47].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these assumptions, it can be concluded that the mechanism of betacyanin degradation may be different, and its variants were initially presented in our publications [41,[43][44][45]. In the course of many years of work on decarboxylated compounds, the above-mentioned and many other structures have been confirmed by LC-MS and/or NMR methods [6,46,47].…”
Section: Introductionmentioning
confidence: 99%
“…A high rate of generation of 2-decarboxy-betanin/-isobetanin, which is present in the BRE extract at a very low level, was observed, which was dependent on the starting concentration of the BRE substrate. The bidecarboxylated derivatives were generated at a higher rate mostly from 17-decarboxy-betanin/-isobetanin as well as 15-decarboxy-betanin by further decarboxylation at carbon C-2 [47].…”
Section: Introductionmentioning
confidence: 99%
“…The bioactive compounds of red beetroots that have been studied in the seven published articles of the Thematic Issue are of a varied nature and activity, ranging from betalains and saponins to phenolic acids and fl avonoids. In this context, the report of Kumorkiewicz et al [2020] presents for the fi rst time the new bidecarboxylated betanins (which might have a strong bioactivities) in red beetroot extract as well as their generation from betanin/isobetanin and mono-decarboxylated betanins during the process of heating. On the other hand, the thermal stability of betalains present in by-products of red beetroot and their degradation along with raising temperature is manifested by the production of various betalain degradation products that have been determined in the work of Otálora et al ponins, being natural plant compounds exhibiting health benefi ts, in red beetroot for the fi rst time using high-speed counter-current chromatography in a new solvent system consisting of tert-butyl-methyl ether-butanol-acetonitrile-water.…”
Section: This Thematic Issue Of Polish Journal Of Food and Nutritionmentioning
confidence: 99%
“…Therefore, natural products comprising biologically active compounds attract much attention [2]. These products implemented into a daily diet may play an important role in the prevention and treatment of many health problems [3]. The violet G. globosa inflorescences are a precious source of many antioxidants involving betalains.…”
Section: Introductionmentioning
confidence: 99%
“…The violet G. globosa inflorescences are a precious source of many antioxidants involving betalains. These compounds are proven to exhibit numerous pro-health properties, owing to the high content of hydroxyl groups that participate in free radical scavenging [3][4][5][6][7]. Their antihemorrhage, antimicrobial, antiinflammatory activity, and analgesic effects have been reported [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%